A Matched-Cohort Population Study of Reoperation After Meniscal Repair With and Without Concomitant Anterior Cruciate Ligament Reconstruction. (February 2013) - Wasserstein, David; Dwyer, Tim; Gandhi, Rajiv; Austin, Peter C.; Mahomed, Nizar; Ogilvie-Harris, Darrell
Background: Evidence for the success of a meniscal repair performed alone versus combined with anterior cruciate ligament reconstruction (ACLR) is equivocal. No large-scale comparative studies exist regarding this issue. Hypothesis: In the general population, meniscal repair in a presumed stable knee has the same rate of reoperation as meniscal repair performed with ACLR. Study Design: Cohort study; Level of evidence, 3. Methods: All meniscal repairs performed with ACLR in Ontario, Canada, between July 2003 and March 2008 in patients aged 15 to 60 years were identified using administrative billing, diagnostics, and procedural coding. This cohort was matched 1:1 for sex, age, and calendar year of surgery with a cohort of patients who underwent meniscal repair alone. The McNemar test of matched pairs was used to compare reoperation rates (debridement or repair) within 2 years of the index procedure. Conditional logistic regression analysis was used to identify potential risk factors for reoperation among unmatched patient (socioeconomic status surrogate, comorbidity) and provider (surgeon volume, academic hospital status) factors. Results: Of 1332 patients who underwent meniscal repair and ACLR, 1239 (93%) were matched with patients who underwent meniscal repair alone. The rate of meniscal reoperation was 9.7% in the combined cohort compared with 16.7% in the repair alone cohort ( P < .0001). In the regression analysis, only ACLR was protective against meniscal reoperation (odds ratio, 0.57; P < .0001). Surgeon volume of meniscal repair did not influence outcome. Conclusion: A meniscal repair performed in conjunction with ACLR carries a 7% absolute and 42% relative risk reduction of reoperation after 2 years compared with isolated meniscal repair.